2013
DOI: 10.3390/ijms14035765
|View full text |Cite
|
Sign up to set email alerts
|

Quick, Selective and Reversible Photocrosslinking Reaction between 5-Methylcytosine and 3-Cyanovinylcarbazole in DNA Double Strand

Abstract: Selective photocrosslinking reaction between 3-cyanovinylcarbazole nucleoside (CNVK) and 5-methylcytosine (mC), which is known as epigenetic modification in genomic DNA, was developed. The reaction was completely finished within 5 s of 366 nm irradiation, and the rate of this photocrosslinking reaction was ca. 30-fold higher than that in the case of unmodified normal cytosine. There were no significant differences in the thermodynamic parameters and the kinetics of hybrid formation of oligonucleotide (ODN) con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 24 publications
(18 reference statements)
1
8
0
Order By: Relevance
“…UPLC analysis after the photosplitting reaction, the peak having the same retention time and the same molecular mass of ORN(Ψ) was appeared (Figure S3). Thus, we concluded that the photocrosslinking reaction to the ORN(Ψ) is photoreversible, the same as the case of U and other unmodified pyrimidine bases in our previous report . This is the first report about the site‐specific chemical reaction toward Ψ in RNA strands.…”
Section: Resultssupporting
confidence: 84%
“…UPLC analysis after the photosplitting reaction, the peak having the same retention time and the same molecular mass of ORN(Ψ) was appeared (Figure S3). Thus, we concluded that the photocrosslinking reaction to the ORN(Ψ) is photoreversible, the same as the case of U and other unmodified pyrimidine bases in our previous report . This is the first report about the site‐specific chemical reaction toward Ψ in RNA strands.…”
Section: Resultssupporting
confidence: 84%
“…As the signal at 170 ppm can be assigned as C4 carbon of thymidine, we assigned signals at 50 and 52 ppm as the carbons attached with Ha or Hc. As the signal at 50 and 52 ppm has the cross peak with 3.8 and 4.4 ppm in 1 H− 13 C HSQC spectrum (Figure S7, Supporting Information), protons having the signal at 3.8 and 4.4 ppm can be assigned as Ha or Hc. Together with 1 H− 1 H NOESY experiment as shown in Figure 3b; i.e., the proton at 3.8 ppm has cross peaks with phenyl proton (2H and 4H) on carbazole ring and the proton at 4.4 ppm did not; we successfully assigned the protons on cyclobutane ring as shown in Figure 3b,c.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“… 13 The photo-cross-linking efficiency between the photo-cross-linkable probe and the target nucleic acid is affected by the amount of energy of the irradiated light. 14 Turbidity is generated in the reaction solution when PPMPs are used, which may reduce the photo-cross-linking reaction rate.…”
Section: Resultsmentioning
confidence: 99%